The case for more American tiny home communities - Guemmer, Jack (My University, 2026)
As affordable housing becomes a fleeting reality for many Americans, it is clear that increasing housing costs pose a significant challenge for current and future generations of homeowners. The issue of affordable housing dates to the 1930s during the Great Depression. Attempts to provide affordable housing have been implemented with limited success by several acts of legislation that ebb and flow with the political climate. However, a strong emergent trend is the commercialization of housing which pits institutional investors against the persons who seek to actually occupy the homes. This study analyzes the possible use of tiny homes situated within cluster home communities to provide more affordable housing options for future first-time homeowners, the homeless and persons who simply want to achieve economic freedom by living in a smaller home. Specifically, this study seeks to answer the question “How can tiny homes be compatibly incorporated into cluster home designed communities so that such homes are accessible and affordable, provide high aesthetics, foster environmental stewardship, and provide a sense of place through spatial layout and amenities?”. This question will be answered using a literature review, projective design, as well as precedent studies. Ultimately, this study aims to provide a comprehensive review of tiny homes in cluster home settings by compiling data (both subjective and objective), categorizing such data, identifying how that data influences four factors, and then drawing a reasonable conclusion supporting that tiny homes in cluster designed communities afford a high level of design, accessibility, community, sustainability and affordability.
Keywords: Tiny homes; Cluster development; Affordable housing